Antigen I/II Participates in the Interactions of Streptococcus suis Serotype 9 With Phagocytes and the Development of Systemic Disease - Auger, Jean-Philippe; Boa, Anaïs-Christelle; Segura, Mariela; Gottschalk, Marcelo (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus suis is an important porcine bacterial pathogen and a zoonotic agent causing a variety of pathologies including sudden death, septic shock, and meningitis. Though serotype 2 is the most studied serotype due to its presence worldwide, serotype 9 is responsible for the greatest number of porcine cases in Spain, the Netherlands, and Germany. Regardless of its increasing importance, very few studies have investigated S. suis serotype 9 virulence factors and pathogenesis. Antigens I/II (AgI/II) are multimodal adhesion proteins implicated in host respiratory tract and oral cavity persistence of various pathogenic human streptococci. It was recently demonstrated that AgI/II is involved in various bacterial functions for serotype 9, participating in the initial steps of the pathogenesis of the infection. However, its contribution to the systemic infection remains unknown. As such, we evaluated herein the role of the S. suis serotype 9 AgI/II in the interactions with phagocytes and the development of systemic disease in a mouse model of infection. Results demonstrated that the presence of AgI/II is important for the development of clinical systemic disease by promoting bacterial survival in blood possibly due to its effect on S. suis phagocytosis, as shown with macrophages and dendritic cells. Furthermore, AgI/II directly participates in dendritic cell activation and pro-inflammatory mediator production following recognition by the Toll-like receptor pathway, which may contribute to the exacerbated systemic inflammation responsible for host death. Taken together, this study demonstrates that the S. suis serotype 9 AgI/II is important for virulence during systemic infection and development of disease. In fact, this is the first study to describe a role of an AgI/II family member in systemic bacterial disease.